2021
DOI: 10.1111/gcb.15887
|View full text |Cite
|
Sign up to set email alerts
|

Lowered nutritional quality of plankton caused by global environmental changes

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
39
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 58 publications
(164 reference statements)
10
39
0
Order By: Relevance
“…Our results are in line with previous studies that showed the association of lower seston nutritional quality with increased cyanobacteria dominance in seston (Senar et al 2019;Schmidt et al 2020). The relative concentrations of DHA, EPA, and overall PUFA of seston in our study were lower than those of seston in northern lakes with DOC concentrations ranging from 2-10 mg•L À1 (Strandberg et al 2015;Lau et al 2021). The seston composition of the boreal lakes reported in Strandberg et al (2015) largely consisted of PUFA-rich cryptophytes and diatoms and to a modest extent of cyanobacteria.…”
Section: Seston Fatty-acid Composition and Qualitysupporting
confidence: 92%
See 1 more Smart Citation
“…Our results are in line with previous studies that showed the association of lower seston nutritional quality with increased cyanobacteria dominance in seston (Senar et al 2019;Schmidt et al 2020). The relative concentrations of DHA, EPA, and overall PUFA of seston in our study were lower than those of seston in northern lakes with DOC concentrations ranging from 2-10 mg•L À1 (Strandberg et al 2015;Lau et al 2021). The seston composition of the boreal lakes reported in Strandberg et al (2015) largely consisted of PUFA-rich cryptophytes and diatoms and to a modest extent of cyanobacteria.…”
Section: Seston Fatty-acid Composition and Qualitysupporting
confidence: 92%
“…Increased browning may promote the development of cyanobacteria and bacteria that lack long-chain PUFA, which may reduce the overall nutritional quality of seston (Taipale et al 2016(Taipale et al , 2018. Reduced seston quality will in turn cause decreases in long-chain PUFA content of zooplankton (Hiltunen et al 2015;Taipale et al 2016Taipale et al , 2018Lau et al 2021). This may consequently lower the marine energy transfer efficiency, but the negative impacts of browning are yet to be verified.…”
Section: Introductionmentioning
confidence: 99%
“…Sampling dates differed among the study sites because of differences in ice-out, stratification, and circulation periods of the lakes. During our sampling period, the study lakes varied in nutrient (total dissolved N [TDN]): 62-439 μg/L; DIN: 1-26.5 μg/L; TP: 3-29 μg/L) and DOC (1.9-20 mg/L) concentrations, and in molar log 10 DIN:TP ratios (0.2-26.5; Table S1; Lau et al, 2021).…”
Section: Site Descriptionmentioning
confidence: 99%
“…Secondly, we hypothesized (H2) that the nutritional quality of seston is decreased by lake trophic status (Keva et al, 2021;Lau et al, 2021;Müller-Navarra et al, 2004;. We also assumed that this decrease in the nutritional quality of primary producers is reflected at different trophic levels via changes in the nutritional quality of their prey.…”
Section: Introductionmentioning
confidence: 99%
“…However, the growing abundance of cyanobacteria blooms in the recent past is related to climate change and especially due to the increased temperature of lakes (Deng et al, 2016; Elliot, 2012; Paerl & Huisman, 2008; Pätynen et al, 2014; Rasconi et al, 2017). Previous studies have shown that a decrease in the nutritional quality of phytoplankton is mainly attributed to the changes by the phytoplankton community structure, but also because the nutritional value of phytoplankton cells decreases by eutrophication (Keva et al, 2021; Lau et al, 2021; Taipale et al, 2019).…”
Section: Introductionmentioning
confidence: 99%